Morbidity and mortality meetings: gold, silver or bronze?. Issue 10 (11th February 2018) - Vreugdenburg, Thomas D.; Forel, Deanne; Marlow, Nicholas; Maddern, Guy J.; Quinn, John; Lander, Richard; Tobin, Stephen
Abstract: Background: Morbidity and mortality (M&M) meetings contribute to surgical education and improvements in patient care through the review of surgical outcomes; however, they often lack defined structure, objectives and resource support. The aim of this study was to investigate the factors that impact the effective conduct of M&M meetings. Methods: We conducted a rapid systematic literature review. Three biomedical databases (PubMed, the Cochrane Library and the University of York Centre for Reviews and Dissemination), clinical practice guideline clearinghouses and grey literature sources were searched from May 2009 to September 2016. Studies that evaluated the function of a hospital‐based M&M process were included. Two independent reviewers conducted study selection and data extraction. Study details and key findings were reported narratively. Results: Nineteen studies identified enablers, and seven identified barriers, to the effective conduct of M&M meetings. Enabling factors for effective M&M meetings included a structured meeting format, a structured case identification and presentation, and a systems focus. Absence of key personnel from meetings, lack of education regarding the meeting process, poor perceptions of the process, logistical issues and heterogeneity in case evaluation were identified as barriers to effective M&M meetings. Conclusion: Taking steps to standardize and incorporate the enabling factors into M&M meetings will ensure that the valuable time spent reviewing M&M is used effectively to improve patient care.